Implementation of Snort as a Wireless Network Security Detection Tool Using Linux Ubuntu - Puteri Puji Insani; Indra Kanedi; Abdussalam Al Akbar (Penerbit Jurnal Indonesia, 2023)
Implementation of snort as a wireless network security detection tool using linux ubuntu by adding a server that is used to observe activities on a wireless network, if there is an activity that is considered dangerous by the client, the information will be stored in the snort log and database. The web-based front-end uses BASE (Basic Analysis and Security Engine) which can be accessed through a browser with the url : IPaddressServer/base/. The information provided is related to attacks detected by snort that have been stored in the database. The information is in the form of source and destination IP addresses, the type of attack that occurred. Based on the tests carried out, it was found that the implementation of snort as a wireless network security detection tool using linux ubuntu can help detect attacks that occur on the network and provide information related to these attacks.